2010
DOI: 10.1371/journal.pone.0012331
|View full text |Cite
|
Sign up to set email alerts
|

Competing Activities of Heterotrimeric G Proteins in Drosophila Wing Maturation

Abstract: Drosophila genome encodes six alpha-subunits of heterotrimeric G proteins. The Gαs alpha-subunit is involved in the post-eclosion wing maturation, which consists of the epithelial-mesenchymal transition and cell death, accompanied by unfolding of the pupal wing into the firm adult flight organ. Here we show that another alpha-subunit Gαo can specifically antagonize the Gαs activities by competing for the Gβ13F/Gγ1 subunits of the heterotrimeric Gs protein complex. Loss of Gβ13F, Gγ1, or Gαs, but not any other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
4
35
0
Order By: Relevance
“…Not surprisingly, modulators of GPCR signaling, such as GRKs, GDIs, GPCR kinases and arrestins, are also encoded in the Drosophila genome. One aspect of Drosophila GPCR signaling that makes it particularly appealing for study is the reduced number of G-proteins -nine genes encode predicted Gα proteins (six have been characterized and three are known only by their CG numbers), three genes encode Gβ proteins and two genes encode Gγ proteins (Table 1) (Katanayeva et al, 2010;Anantharaman et al, 2011). Of the three Gα subunits with only CG designations, one appears to be a pseudogene (CG40005) and the other two are not expressed in embryos (CG30054 and CG17760).…”
Section: Drosophila Gpcrsmentioning
confidence: 99%
“…Not surprisingly, modulators of GPCR signaling, such as GRKs, GDIs, GPCR kinases and arrestins, are also encoded in the Drosophila genome. One aspect of Drosophila GPCR signaling that makes it particularly appealing for study is the reduced number of G-proteins -nine genes encode predicted Gα proteins (six have been characterized and three are known only by their CG numbers), three genes encode Gβ proteins and two genes encode Gγ proteins (Table 1) (Katanayeva et al, 2010;Anantharaman et al, 2011). Of the three Gα subunits with only CG designations, one appears to be a pseudogene (CG40005) and the other two are not expressed in embryos (CG30054 and CG17760).…”
Section: Drosophila Gpcrsmentioning
confidence: 99%
“…As in C. elegans, Gbg dimers are involved in the control of asymmetric cell division in neuroblasts and sensory organs, gastrulation, heart function (Schaefer et al, 2001;Izumi et al, 2004;Yi et al, 2006Yi et al, , 2008, and the visual system (Dolph et al, 1994;Schulz et al, 1999). One study suggested that free Gbg subunits are involved in wing expansion accompanied by epithelial-mesenchymal transition (Katanayeva et al, 2010). Beyond this role in early development, Gbg subunits also serve other canonical roles in GPCR signaling in the adult fly, as in C. elegans.…”
Section: B Invertebrate Gbgmentioning
confidence: 99%
“…Indeed, in the brain Gbg released from the Go complex is able to regulate voltage-dependent Ca 2+ channels, as well as inward-rectifier K + channels [132]. However, through several broad screening approaches we have identified a massive network of Gao-centered protein-protein interactions ( [121,133] and unpublished data). Two novel Gao target proteins will be reviewed below: Rab5 and Axin.…”
Section: The Heterotrimeric Go Protein: Captain and His Crewmentioning
confidence: 97%